Carbon@SiC(SiCnws)-Sc2Si2O7 ceramics with multiple loss mediums for improving electromagnetic shielding performance. Issue 5 (May 2022) - Wei, Hanjun; Yu, Yaping; Jiang, Fengrui; Xue, Jimei; Zhao, Feng; Wang, Qingyuan
Abstract: Multiple loss media can be applied, not only to improve the performance of microwave absorption materials, but also to promote the electromagnetic (EM) shielding efficacy of materials. In this study, multiple loss mediums (C, SiC, and SiCnws) were introduced into Sc2 Si2 O7 ceramics to synthesise carbon@SiC(SiCnws)-Sc2 Si2 O7 ceramics by H2 reduction and CVI technology. After 1–3 CVI process cycles, the open porosity decreases from 34.7 %±0.5 % to 8.4 %±0.3 % filled with multiple loss media. The results show that CH3 SiCl3 provides the raw material for synthesising SiC(SiCnws) and carbon in ceramics, resulting in adjustable EM shielding properties. Furthermore, the EM shielding mechanism consists mainly of the combined synergistic effect of C, SiC, and SiCnws, which contributes to the reflective shielding efficacy, and promotes the absorption shielding effectiveness, including dipole polarization loss, and interface polarization loss. Subsequently, carbon@SiC(SiCnws)-Sc2 Si2 O7 ceramics with a multiple loss medium of 31.2 wt% ±0.22 wt% achieve a total EM shielding effectiveness value of 31.8 dB (99.92 % electromagnetic waves are attenuated) with an X-band thickness of 2 mm. Therefore, carbon@SiC(SiCnws)-Sc2 Si2 O7 ceramics are a promising novel composite, applicable in future EM shielding in high temperature environments.